(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Most of the social reformers tried to uplift and restore the women’s glory through preaching, press and platform. Among them a few notable reformists are raja ram mohan roy, iswarachandra vidya sagar, swami dayanad, kandukuri veersalingam, duragabai deshmukh, jyotiba phule and ramaswami. Raja ram mohan roy succeeded in making viceroy lord wiliam bentick, to declare the sati system illegal. In the patriarchal family and society of our country for centuries, the law of manu in regard to the role and behavior of women have been rigidly adhered. The state never set out to restructure rectious of authority within the family or other resources .for many political and academic reasons the specificity of women’s oppression and exploitation and role of the state remained substantially unexamined to bring an end to the oppression of women in our country, several reformers tried their best to influence the state. nevertheless, it was Ambedkar who had been successful to influence the state to come the rescue of the women of our country. The purpose of the present chapter is to examine Dr. Ambedkar’s efforts in understanding the complete reality about the status of women in India through a comprehensive hindu code bill was on his pragmatic approach to recognize, restructure and reform the patriarchal family for repairing the dilapidated component of Indian society , namely, the women.